Control of magnetoelastic coupling in Ni/Fe multilayers using He+ion irradiation - Masciocchi, Giovanni; Van Der Jagt, J. W.; Syskaki, M-A; Lamperti, Alessio; Wolff, Niklas; Lotnyk, Andriy; Langer, Juergen; Kienle, L.; Jakob, Gerhard; Borie, Benjamin; Kehlberger, A.; Ravelosona, D.; et al. (Applied Physics Letters, 2022)
This study reports the effects of post-growth He+ irradiation on the magneto-elastic properties of a Ni/Fe multi-layered stack. The progressive intermixing caused by He+ irradiation at the interfaces of the multilayer allows us to tune the saturation magnetostriction value with increasing He+ fluences and even to induce a reversal of the sign of the magnetostrictive effect. Additionally, the critical fluence at which the absolute value of the magnetostriction is dramatically reduced is identified. Therefore, insensitivity to strain of the magnetic stack is nearly reached, as required for many applications. All the above-mentioned effects are attributed to the combination of the negative saturation magnetostriction of sputtered Ni and Fe layers and the positive magnetostriction of the NixFe1-x alloy at the intermixed interfaces, whose contribution is gradually increased with irradiation. Importantly, the irradiation does not alter the layer polycrystalline structure, confirming that post-growth He+ ion irradiation is an excellent tool to tune the magneto-elastic properties of multilayer samples. An alternative class of spintronic devices can be envisioned with a material treatment able to arbitrary change the magnetostriction with ion-induced "magnetic patterning".
CRIS-Team Scopus Importer:2023-03-27